The moderating role of loneliness on the relationship between loot box engagement on problematic gaming behavior and gambling behavior - Santos, Michelle Nicole Pasion (Animo Repository, 2023)
The COVID-19 Pandemic forced many individuals to stay home and practice social distancing. One way to combat loneliness was to play games. The increasing implementation of loot box systems in modern games can expose gamers to problematic gaming and gambling behaviors. This study investigated the moderating role of loneliness in the relationship between loot box engagement and problematic gaming behavior and problem gambling behavior among gamers in the Philippine setting. The study used a predictive cross-sectional design and analyzed 91 participants who have regularly engaged with loot box systems. Despite the small sample size, the study has acceptable power based on a compromise power analysis. The results suggested that loot box engagement positively predicts both gambling and gaming behaviors and that loneliness moderates the relationship of loot box to gambling but not the relationship of loot boxes to gaming. The findings of this study may have implications for the benefit of gamers, game publishers and developers, clinical practitioners, and future researchers. The present study can contribute to the development of interventions aimed at reducing problematic gaming behavior and problem gambling behavior among gamers. Keywords: loneliness, loot box engagement, problematic gambling behavior, problematic gaming behavior